Amplitudes of Pain-Related Evoked Potentials Are Useful to Detect Small Fiber Involvement in Painful Mixed Fiber Neuropathies in Addition to Quantitative Sensory Testing – An Electrophysiological Study - Hansen, Niels; Kahn, Ann-Kathrin; Zeller, Daniel; Katsarava, Zaza; Sommer, Claudia; Üçeyler, Nurcan (Frontiers in Neurology, 2015)
To investigate the usefulness of pain-related evoked potentials (PREP) elicited by electrical stimulation for the identification of small fiber involvement in patients with mixed fiber neuropathy (MFN). Eleven MFN patients with clinical signs of large fiber impairment and neuropathic pain and ten healthy controls underwent clinical and electrophysiological evaluation. Small fiber function, electrical conductivity and morphology, were examined by quantitative sensory testing (QST), PREP and skin punch biopsy. MFN was diagnosed following clinical and electrophysiological examination (chronic inflammatory demyelinating neuropathy: n=6; vasculitic neuropathy: n=3; chronic axonal neuropathy: n=2). The majority of patients with MFN characterized their pain by descriptors that mainly represent C-fiber-mediated pain. In QST, patients displayed elevated cold, warm, mechanical, and vibration detection thresholds and cold pain thresholds indicative of MFN. PREP amplitudes in patients correlated with cold (p<0.05) and warm detection thresholds (p<0.05). Burning pain and the presence of par-/dysesthesias correlated negatively with PREP amplitudes (p<0.05). PREP amplitudes correlating with cold and warm detection thresholds, burning pain, and par-/dysesthesias support employing PREP amplitudes as an additional tool in conjunction with QST for detecting small fiber impairment in patients with MFN.